Survival benefit of lymphadenectomy for gallbladder cancer based on the therapeutic index: An analysis of the US extrahepatic biliary malignancy consortium. Issue 3 (6th January 2020) - Sahara, Kota; Tsilimigras, Diamantis I.; Maithel, Shishir K.; Abbott, Daniel E.; Poultsides, George A.; Hatzaras, Ioannis; Fields, Ryan C.; Weiss, Matthew; Scoggins, Charles; Isom, Chelsea A.; Idrees, Kamran; Shen, Perry; et al.
Abstract: Background: The survival benefit of lymphadenectomy among patients with gallbladder cancer (GBC) remains poorly understood. Methods: Patients who underwent resection for GBC between 2000 and 2015 were identified from a US multi‐institutional database. The therapeutic index (LNM rate multiplied by 3‐year overall survival [OS]) was determined to assess the survival benefit of lymphadenectomy. Results: Among 449 patients, less than half had LNM (N = 183, 40.8%). The median number of evaluated and metastatic lymph nodes (LNs) was 3 (interquartile range [IQR]: 1‐6) and 1 (IQR: 0‐1), respectively. 3‐year OS among patients with LNM in the entire cohort was 26.8%. The therapeutic index was lower among patients with T4 (5.9) or T1 (6.0) tumors as well as carbohydrate antigen (CA19‐9) ≥200 UI/mL (6.0). Of note, a therapeutic index difference ≥10 was noted relative to CA19‐9 (<200: 18.7 vs ≥200: 6.0), American Joint Committee on Cancer T Stage (T1: 6.0 vs T2: 17.8 vs T4: 5.9) and number of LNs examined (1‐2: 6.9 vs ≥6: 16.9). Concomitant common bile duct resection was not associated with a higher therapeutic index among patients with either T2 or T3 disease. Conclusion: Certain clinicopathological factors including T1 or T4 tumor and CA19‐9 ≥200 UI/mL were associated with a low therapeutic index. Resection of six or more LNs was associated with a meaningful therapeutic index benefit among patients with LNM.